A BRIEF STUDY OF DIFFERENT HEAT EXCHANGERS WITH SPECIAL REFERENCE TO GASKETED TYPE PLATE HEAT EXCHANGER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2019)
The plate and frame or gasket plate heat exchanger (PHE) consists of number of thin rectangular metal plates sealed around the edges by gaskets and held together in a frame. The frame usually has a fixed end cover (headpiece) fitted with connecting ports and a moveable end cover (pressure plate, follower, or tailpiece). In the frame, the plates are suspended from an upper carrying bar and guided by a bottom carrying bar to ensure proper alignment. For this purpose, each plate is notched at the center of its top and bottom edges. The plate pack with fixed and movable end covers is clamped together by long bolts, thus compressing the gaskets and forming a seal. For later discussion., we designate the resulting length of the plate pack as Lpack . The carrying bars are longer than the compressed stack, so that when the movable end cover is removed, plates may be slid along the support bars for inspection and cleaning.